The Compassionate Engagement and Action Scales for Self and Others: Turkish Adaptation, Validity, and Reliability Study - Ari, Ela; Cesur-Soysal, Gizem; Basran, Jaskaran; Gilbert, Paul (Frontiers in Psychology, 2022)
Aim: This study aims to adapt the Compassionate Engagement and Action Scales (CEAS) into Turkish and to test the subsequent validity, reliability, and psychometric properties. Turkey is one of the blend cultures with eastern and western elements under the influence of traditional religion. This cultural diversity brings a rich context to study compassion and mental health relation. The scales assess the ability to be sensitive to suffering and engagement in compassion. The motivation for compassionate engagement and action is measured at three levels: 1. Compassion for others; 2. Compassion from others; and 3. Compassion for self. Methods: The sample consists of 525 college students who were 18 or older. The participants completed the CEAS Turkish Form for Others, Self and from Others, Self-Compassion Scale Short Form, Compassionate Love Scale, Self-Criticism Scale. Results: Confirmatory factor analyses were conducted using AMOS v.27 to examine the validity of the three scales with two different factor structures each. All the three models show good fits to the data. The Cronbach Alpha coefficient for the CEAS for Others, for Self and from Others are good to excellent (between .70 and .95 for all subscales). Compassion for self, compassion for others, and compassion from others correlated modestly. Conclusion: It can be concluded that the Turkish version of the Compassionate Engagement and Action Scales for Others, Self and from Others has sufficient psychometric properties and can be used as a reliable and valid tool to assess compassionate engagement and action.